Image of Jamu Madura Differences Review From Respondents Experience - Herawati, Netty; Rohmah, Nailur; Hutagalung, Fonny D. (Procedia of Social Sciences and Humanities, 2024)
This study to see the differences in the image of madurai was reviewed from the experience of respondents. This is a quantitatif research. The sample collection in this study is purposive sampling, the criterion of respondents is respondents know about Madura, respondents have never/never consumed Madura. Respondents of adult age, the respondents are from two countries namely Malaysia and Indonesia. data collection using the ordinal scale of Likert. Data analysis techniques use the help of SPSS applications using T-Test tests as static tests for the proof of hypotheses. The results showed a t value of -5,852 with a significance of 0,00 (0,05) meaning that there was a significant difference in the image of Madura's juice reviewed from the respondent's experience. Experience respondents who have consumed Madura spices have a positive image and, on the contrary, respondents that have never consumed madura spice have a negative image.